International Law and Cyber Technology: Challenges of Global Regulation in the Digital Diplomacy Era - Dewi Triwahyuni; Wim Tohari Daniealdi; Iwan Ridwan Zaelani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid development of information technology has driven a major transformation in international relations, particularly through digital diplomacy. On the other hand, this progress has also posed serious challenges to international law, which has yet to fully regulate cross-border cyber activities. This study aims to examine the main challenges faced by international law in responding to the dynamics of global cyberspace, as well as to evaluate the role of digital diplomacy in shaping fair and inclusive cyber regulations. The research employs a qualitative method using a literature review approach, analyzing scholarly sources, policy reports, and official international documents. The findings reveal a significant legal vacuum in addressing cyberattack attribution, state responsibility, and the protection of human rights in the digital space. Current cyber diplomacy efforts remain hindered by ideological differences between major powers and developing countries, as well as by the dominance of non-state actors such as global technology companies. The conclusion of this study highlights the urgency of establishing a responsive, multistakeholder international legal framework that ensures global digital justice. Without collective efforts and international compromise, cyberspace risks becoming a battlefield of conflict without clear legal boundaries.